Change of climate conditions in the forest area of South Yakutia; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Reshetko M. V. Margarita Viktorovna (Geology, Hydrogeology and Engineering Geology, 2016)
Title screen